Abschlussbericht Software für ein Risiko-Management-System - Wilke, Peter; et al. (2002)
UnivIS-Import:2016-06-30:Pub.2002.tech.IMMD.IMMD2._absch
Keywords: Risiko-management-system

A Distributed Network Simulation Environment for Multi-Processing Systems - Jacob, Christian; Wilke, Peter (Proceedings of the IEEE International Joint Conference on Neural Networks (IJCNN'91), 1991)
A simulator for neural network models is presented which is based on the X Window System programming environment and allows interactive construction of many different network models. The visualization of net topologies and parameters is handled by graphic workstations. Furthermore, the simulator is capable of using a multiprocessing system to perform time-consuming net control algorithms, which have been especially designed to efficiently use the underlying hardware. Several tools are being implemented for controlling the distribution of computational tasks, performed on a neural network, among the available processors
UnivIS-Import:2017-01-09:Pub.1991.tech.IMMD.IMMD2._adist_4

A General View on Timetabling Problems - Gröbner, Matthias; Wilke, Peter (Proc. 4th Int. Conference on the Practice and Theory of Automated Timetabling IV, 2003)
UnivIS-Import:2017-07-10:Pub.2003.tech.IMMD.IMMD5.agener
Keywords: timetabling

A Hybrid Genetic Algorithm for School Timetabling - Wilke, Peter; Gröbner, Matthias; Oster, Norbert (AI 2002: Advances in Artificial Intelligence - 15th Australian Joint Conference on Artificial Intelligence, 2002)
Hybrid Genetic Algorithms apply so called hybrid or repair operators or include problem specific knowledge about the problem domain in their mutation and crossover operators. These operators use local search to repair or avoid illegal or unsuitable assignments or just to improve the quality of the solutions already found. Those Hybrid Genetic Algorithms have been successfully applied to different constraint satisfaction and timetabling problems such as the travelling salesman problem, scheduling problems, employee timetabling or high school timetabling. In this paper we describe a Genetic Algorithm for solving the German school timetabling problem. The Genetic Algorithm uses direct representation of the problem and applies an adapted mutation operator as well as several specific repair operators. We redecode the computed improvements to the genotype which establishes a kind of Lamarckian evolution. One of the problems utilising these hybrid operators is how and when to apply them, i.e. how to set the parameters right to achieve the best results. Different approaches have been started to adjust these parameters in an optimal way, but in most cases these adjustments require additional computing time and consequently are quite costly. We tackled this problem by an adaptation mechanism for the repair operators which can be applied without additional computing time. These operators are switched on when the normal Genetic Algorithm does not yield any more improvements. When the Genetic Algorithm then converges again, a reconfiguration step for the operator parameters guides the search out of the local optimum.

A Neural Network Simulation Environment with Components for Genetic Algorithms and Fuzzy Logic - Wilke, Peter (1994)

An Integrated Development Environment for Neural Networks, Genetic Algorithms and Fuzzy Logic - Wilke, Peter (Proceedings of the Third European Congress on Intelligent Techniques and Soft Computing (EUFIT'95), 1995)

An Integrated Framework for Distributed Timetabling - Wilke, Peter (Proc. 6th Int. Conf. on the Pratice and Theory of Automated Timetabling (PATAT 2006), 2006)

A Standard Framework for Timetabling Problems - Gröbner, Matthias; Wilke, Peter; Büttcher, Stefan (Practice and Theory of Automated Timetabling - 4th International Conference (PATAT 2002), 2003)

Bedienhandbuch für NeuroGraph Version 3.0 - Wilke, Peter (1994)

Binding of the RNA polymerases from Rhizobium leguminosarum 300 and Escherichia coli to the hybrid plasmid pSA31 - Wilke, Peter; Raschke, Eberhard; Lotz, Wolfgang; Cannon, F. C. (Proceedings of the 8th North American Rhizobium Conference, 1981)

CANTOR - The implementation of a set theoretic concept - Wilke, Peter (Rencontres des etablissements de recherche en informatique des villes jumelees avec Rennes, 1991)

Comparison of Algorithms solving School and Course Time Tabling Problems using the Erlangen Advanced Time Tabling System (EATTS) - Wilke, Peter; Killer, Helmut (Proc. PATAT 2010, 2010)

Definition der mengentheoretischen Programmiersprache CANTOR - Wilke, Peter (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1988)
UnivIS-Import:2016-07-26:Pub.1988.tech.IMMD.IMMD2._defin

Definition einer Syntax für eine mengentheoretische Programmiersprache - Wilke, Peter (1985)
UnivIS-Import:2016-06-23:Pub.1985.tech.IMMD.IMMD2._defin

Design and Implementation of Neural Networks for Matching Contours in CAD Models - Wilke, Peter; Geiger, H; Greska, Wolfgang; Behrendtz, Jürgen (Proceedings of the International Conference on Artificial Neural Networks (ICANN 94), 1994)

Entwicklung eines Software-Werkzeuges für Risiko-Management - Wilke, Peter; Schnaittinger, T.; Werner, F.; Lampka, K.; Grosser, N. (2001)
UnivIS-Import:2016-06-30:Pub.2001.tech.IMMD.IMMD2._entwi
Keywords: Entwicklung; Software; Werkzeug; Risiko-Management

Entwurf und Implementierung der mengentheoretischen Programmiersprache CANTOR - Wilke, Peter (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1988)

Erkennung von Blechteilen mit Neuronalen Netzen - Wilke, Peter; Geiger, H; Greska, Wolfgang; Behrendtz, Jürgen (Zeitschrift für Wirtschaftliche Fertigung und Automatisierung, 1993)

Fehlerklassifikation auf Röntgenbildbasis - Wilke, Peter; Feldmann, Klaus; Götz, Knuth (Tagungsband Symposium Anwendung von Fuzzy-Technologien und Neuronalen Netzen, 1996)

Flexible wireless communication network for mobile robot agents - Wilke, Peter; Bräunl, Thomas (Industrial Robot: An International Journal, 2001)
For intelligent robots in a multi‐agent system communication is essential for cooperative behavior. Here we describe the explicit communication between individual robots acting as team members of a RoboCup team playing soccer. The robots are based on the EyeBot platform. An overview of communication systems being published and a discussion of their advantages and drawbacks is followed by an introduction into multi‐agent systems and the problems we faced applying them to the task of playing soccer. Then we describe the wireless communication network in detail including the EyeBot platform, message structures, self‐configuration and error recovery. The communication allows transmission of messages between individuals, broadcasts and communication with a remote computer workstation. The communication system is a layer beneath the multi‐robot console, which is the user interface, and above the EyeBot hardware.

FLEXMAP - A neural network with linear time and space complexity for the travelling salesman problem - Fritzke, Bernd; Wilke, Peter (Proceedings of the IEEE International Joint Conference on Neural Networks (IJCNN'91), 1991)
The authors present a self-organizing `neural' network for the traveling salesman problem. It is partly based on the model of Kohonen. The proposed approach differs from former work in this direction as no ring structure with a fixed number of elements is used. Instead a small initial structure is enlarged during a distribution process. This makes it possible to replace the central search step, which normally needs time O(n), by a local procedure that needs time O (1). Since the total number of search steps that must be performed is O(n) the runtime of the model scales linearly with problem size. This is better than every known neural or conventional algorithm. The path lengths of the solutions generated are less than 10% longer than the optimum solutions of solved problems from the literatu

Handbuch für NeuroGraph Version 3.4 - Wilke, Peter (1994)

Handbuch für NeuroGraph Version 3.6 - Wilke, Peter (1996)

Integration of Genetic Algorithms and Fuzzy Logic into a Neural Network Simulation Environment, Analysis and Simulation of Computer and Telecommunication Systems - Wilke, Peter; Billing, Gunnar; Mansfeld, Christian; Nilson, Jörg (Proc. Int. Workshop on Modelling, MASCOTS95, 1995)

Integration of Genetic Algorithms and Fuzzy Logic into a Neural Network Simulation Environment - Wilke, Peter; Billing, Gunnar; Mansfeld, Christian; Nilson, Jörg (Proceedings of the 3rd International Workshop on Modeling, Analysis, and Simulation of Computer and Telecommunication Systems (MASCOTS'95), 1995)
NEUROGRAPH is a simulation environment for neural networks. It provides an easy to use graphical user interface to design, construct and execute neural networks. The most important design goals were easy extensibility, good performance and the ability to solve real world problems. Extensibility is ensured by an extremely flexible, hierarchical internal representation (data structure), which can be easily manipulated by graphical tools. Current available extensions to the neural network simulator are components for genetic algorithms and fuzzy logic. As an example the automated generation of a neural network by a genetic algorithm is shown. This data structure can be interpreted for debugging purposes or can be executed directly for high performance computing. In the later case C or C++ code is generated from the internal representation of the neural functions, compiled and stored in an executable process (library). NEUROGRAPH has a file or process interface to interconnect which other processes. It is also possible to generate C or C++ code representing the neural network which can be incorporated in other applications

Marktübersicht Simulatoren für neuronale Netze auf PCs, Workstations und verteilten Rechnersystemen - Wilke, Peter; Sonnefeld, Ralf (VDE Verlag, 1995)

Marktübersicht Simulatoren für Soft-Computing-Systeme auf PCs - Wilke, Peter; Sonnefeld, Ralf; Metin, M. (1996)

Marktübersicht Simulatoren für Soft-Computing-Systeme auf PCs, Workstations und verteilten Rechnersystemen - Wilke, Peter; Sonnefeld, Ralf (1995)

Neural Networks Matching Contours in CAD Models - Wilke, Peter; Greska, Wolfgang; Geiger, Manfred; Berentz, Jörg (1994)

NeuroGraph 2.0 Handbuch - Wilke, Peter (1993)
UnivIS-Import:2016-06-23:Pub.1993.tech.IMMD.IMMD2._neuro_35

NeuroGraph - A Neural Network Simulation Environment - Wilke, Peter (Workshop Neural Network Simulation, 1993)

NeuroGraph - A Neural Network Simulation Environment with Components for Genetic Algorithms and Fuzzy Logic - Wilke, Peter (Proc. 39. wiss. Kolloquium TU Ilmenau, 1994)

NeuroGraph - An Integrated Development Environment for Neural Networks - Genetic Algorithms and Fuzzy Logic - Wilke, Peter; Rehder, Jan; Billing, Gunnar; Nilson, Jörg; Mansfeld, Christian (EUFIT95, 1995)

NeuroGraph - A Simulation Environment for Neural Networks, Genetic Algorithms and Fuzzy Logic - Wilke, Peter; et al. (Artificial Neural Nets and Genetic Algorithms - Proceedings of the International Conference (ICANNGA'95), 1995)

NeuroGraph - Ein Simulator für künstliche Neuronale Netze auf paralleler Hardware - Wilke, Peter (ASIM93, 1993)

NeuroGraph - Ein Simulator für künstliche Neuronale Netze auf paralleler Hardware - Wilke, Peter (Proc. 8. ASIM Symposium Simulationstechnik, 1993)

NeuroGraph - Ein Simulator für künstliche Neuronale Netzeauf paralleler Hardware - Wilke, Peter; Scholz, R. (PASA93, 1993)

NeuroGraph - Ein Simulator für künstliche Neuronale Netze auf paralleler Hardware - Wilke, Peter; Scholz, Ralf (Proceedings of the 3. PASA-Workshop Parallele Systeme und Algorithmen, 1993)

NeuroGraph Neural Network Simulator V3.0 - Wilke, Peter; et al. (1994)

NeuroGraph V3.4 Bedienhandbuch - Wilke, Peter; et al. (1995)
UnivIS-Import:2016-06-27:Pub.1995.tech.IMMD.IMMD2._neuro_9

NeuroGraph V3.4 User's Manual - Wilke, Peter; et al. (1995)
UnivIS-Import:2016-06-27:Pub.1995.tech.IMMD.IMMD2._neuro_5

NeuroGraph V3.6 Bedienhandbuch - Wilke, Peter; et al. (1996)
UnivIS-Import:2016-06-27:Pub.1996.tech.IMMD.IMMD2._neuro

NeuroGraph V3.6 Users Manual - Wilke, Peter (1996)

Neuronale Netze zur Konturanalyse in CAD-Modellen - Greska, Wolfgang; Wilke, Peter; Geiger, Manfred; Berentz, Jörg (Zeitschrift für Wirtschaftliche Fertigung und Automatisierung, 1994)

Optimization of Flow-Shop Problems using Evolutionary Algorithms - A Case Study - Wilke, Peter; Zobel, Matthias (Proc. European Conference for Intelligent Technologies (EUFIT'97), 1997)

Optimizing Employee Schedules by a Hybrid Genetic Algorithm - Gröbner, Matthias; Wilke, Peter (Applications of Evolutionary Computing EvoWorkshops 2001: EvoCOP, EvoFlight, EvoIASP, EvoLearn, and EvoSTIM, 2001)

Programmierhandbuch für NeuroGraph Version 3.0 - Wilke, Peter (1994)

Programmiersprachen mit Mengenkonzept für unkonventionelle Hardware - Wilke, Peter; Schneider, Hans Jürgen; Völk, Andreas (1985)
UnivIS-Import:2016-06-23:Pub.1985.tech.IMMD.IMMD2._progr

Prozessbegleitende Qualitätssicherung in der Elektronikproduktion - Wilke, Peter; Feldmann, Klaus; Götz, Knuth (Tagungsband Symposium Anwendung von Fuzzy Technologien und Neuronalen Netzen, 1996)
UnivIS-Import:2017-01-09:Pub.1996.tech.IMMD.IMMD2._proze

Rostering with a Hybrid Genetic Algorithm - Gröbner, Matthias; Wilke, Peter (Artificial Neural Nets and Genetic Algorithms Proceedings of the International Conference, 2001)

Simulating Neural Networks in a Distributed Computing Environment Using NeuroGraph - Wilke, Peter; Jacob, Christian (Proceedings of the International Workshop on Modeling, Analysis, and Simulation On Computer and Telecommunication Systems (MASCOTS'93), 1993)

Simulation künstlicher neuronaler Netze - Wilke, Peter (Arbeitsgemeinschaft Funktionalanalysis, Universität Erlangen-Nürnberg, 1992)

Simulation of Marburg Model Neural Networks using NeuroGraph - Wilke, Peter; Gröbner, Matthias (Proc. World Congress on Scientic Computation, Modelling and Applied Mathematics (IMACS 97), 1997)

Simulation of Neural Network: ... or the dark side of computational power - Wilke, Peter (University of Western Australia, 1999)

Simulation of Neural Networks and Genetic Algorithms in a Distributed Computing Environment using NeuroGraph - Wilke, Peter (World Congress on Neural Networks, 1993)

Simulation of Neural Networks and Genetic Algorithms in a Distributed Computing Environment using NeuroGraph - Wilke, Peter (Proceedings of the International Conference on Artificial Neural Networks (ICANN'93), 1993)

Simulation of Neural Networks in a Distributed Computing Environment using NeuroGraph - Wilke, Peter (Proc. IWANN93 Int. Workshop on Artificial Neural Networks, 1993)

Simulation of Neural Networks in a Distributed Computing Environmentusing NeuroGraph - Wilke, Peter (1993)

Simulation of Neural Networks in a Distributed Computing Environmentusing NeuroGraph - Wilke, Peter (1993)

Simulation of Neural Networks in a Distributed Computing Environment using NeuroGraph - Wilke, Peter (Proceedings of the 6th Italian Conference on Neural Networks (WIRN'93), 1993)

Simulation of Neural Networks in a Distributed Computing Environment using NeuroGraph - Wilke, Peter (Proceedings of the 1993 Conference on Computation and Neural Systems (CNS*93), 1993)

Simulation of Neural Networks in a Distributed Computing Environment using NeuroGraph - Wilke, Peter (New Trends in Neural Computation: International Workshop on Artificial Neural Networks (IWANN'93), 1993)

Simulation und Visualisierung künstlicher neuronaler Netze unter Verwendung paralleler Hardware - Wilke, Peter; Jacob, Christian (1992)
UnivIS-Import:2016-06-23:Pub.1992.tech.IMMD.IMMD2._simul_0

Simulation und Visualisierung künstlicher neuronaler Netze unter Verwendung paralleler Hardware mit NeuroGraph - Wilke, Peter; Jacob, Christian; Scholz, Ralf (Proceedings of the Economic Parallel Processing (EPP'93), 1993)

Simulation und Visualisierung künstlicher neuronaler Netze unter Verwendung paralleler Hardware mit NeuroGraph - Wilke, Peter; Scholz, Ralf (Proceedings des Europäischen Informatik-Kongresses Architektur von Rechensystemen (Euro-ARCH 1993), 1993)

Soft-Computing - Prinzip - Wilke, Peter (1997)

Soft-Computing - Prinzip, Simulation und Anwendung - Wilke, Peter (1997)

Software für RISC, optimierende Compiler - Wilke, Peter (RISC-Architekturen, Reihe Informatik, vol. 60, 1988)

Software für RISC: optimierende Compiler - Wilke, Peter (RISC-Architekturen: Systeme, optimierende Compiler, Anwendungen, Leistungsmessung, Parallelismus, 1990)

Solving the School Time Tabling Problem Using Tabu Search, Simulated Annealing, Genetic and Branch & Bound Algorithms - Wilke, Peter; Ostler, Johannes (PATAT '08 Proceedings of the 7th International Conference on the Practice and Theory of Automated Timetabling, 2008)

The Erlangen Advanced Time Tabling System (EATTS) Unified XML File Format for the Specification of Time Tabling Systems - Wilke, Peter; Ostler, Johannes (Proc. PATAT 2010, 2010)

The Erlangen Advanced Time Tabling System (EATTS) version 5 - Wilke, Peter; Ostler, Johannes; Merdenoglu, Kerim; Kremer, Eugen; Killer, Helmut (Proc. PATAT 2010, 2010)

The NeuroGraph Neural Network Simulator - Jacob, Christian; Wilke, Peter (Proceedings of the International Workshop on Modeling, Analysis, and Simulation On Computer and Telecommunication Systems (MASCOTS 1993), 1993)

Time Series Prediction for Workforce Management Systems for Call Centres - Wilke, Peter; Glaser, Günter (Proc. Second ICSC Symposium on Neural Computation NC2000, 2000)

Verteilte Simulation Neuronaler Netze mit NeuroGraph V3.0 - Wilke, Peter; Scholz, R. (1994)

Verteilte Simulation Neuronaler Netze mit NeuroGraph V3.0 - Wilke, Peter; Scholz, Ralf (Proc. Transputer Anwender Treffen (TAT94), 1994)

Visualization of Neural Networks using NeuroGraph - Wilke, Peter (Visualization in Scientific Computing, 1993)

Visualization of Neural Networks using NeuroGraph - Wilke, Peter (Proceedings of the IFIP WG3.2 Working Conference on Visualization in Scientific Computing: Uses in University Education, 1993)

Visualization of Neural Networks using NeuroGraph, Uses in University Education - Wilke, Peter (Proc. IFIP Working Group 3.2 Working Conference on Visualization in Scientific Computing, 1993)

Walk Up Jump Down - a new Hybrid Algorithm for Time Tabling Problems - Wilke, Peter; Killer, Helmut (Proc. PATAT 2010, 2010)

Zusammenhänge und Unterschiede zwischen Graph-Grammatiken und Petri-Netzen sowie verwandter Systeme Arbeitsberichte des IMMD der Universität Erlangen-Nürnberg - Wilke, Peter (1983)

Zusammenhänge und Unterschiede zwischen Graph-Grammatiken und Petri-Netzen sowie verwandter Systeme - Wilke, Peter (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1983)

Zusammenhänge und Unterschiede zwischen Graph-Grammatiken und Petri-Netzen sowie verwandter Systeme - Wilke, Peter (1997)

Zwischenbericht Entwicklung eines Software Werkzeuges für Risiko-Management - Wilke, Peter; et al. (2001)